Educational Excellence and Strategiec Promotion: Strengthening Islamic School Branding through 7P Integration - Mahmud MY; Fadlilah Fadlilah; Suci Fitriani; Fransisko Chaniago; Sizka Farwati; Sri Ramdayeni Sakunti (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
This research investigates the strategic efforts of Madrasah Tsanawiyah Darul Arifin to enhance its branding image through the application of the 7P Marketing Mix framework: Product, Price, Place, Promotion, People, Process, and Physical Evidence. In an increasingly competitive Islamic education sector, effective branding is crucial for establishing institutional credibility, increasing enrollment, and fostering public trust. The study adopts a qualitative descriptive approach using data collected through interviews, observation, and documentation. Key informants include school leaders, administrative staff, academic personnel, students, and community members. The analysis reveals that the leadership of the Kyai, the implementation of flagship programs, consistent promotion strategies, and the quality of physical infrastructure significantly shape the institution’s brand image. These flagship programs serve as key differentiators in the competitive education market, emphasising both academic excellence and religious devotion. The institution’s commitment to producing well-rounded students competent in Islamic knowledge, languages, and leadership has strengthened its positioning as a leading Islamic educational institution. Findings show that the figure of the Kyai serves as a moral and symbolic leader, fostering public trust and social legitimacy. The madrasah’s flagship programs function as academic differentiators that attract both urban and rural communities. Promotional efforts, including social media and alums networks, expand the madrasah’s visibility while maintaining its spiritual values. The registration process reflects administrative professionalism, and the well-maintained facilities support both educational effectiveness and brand positioning. This study concludes that a strong brand image in Islamic education is built not only through visibility but through integrated, value-based institutional management. The 7P framework provides a comprehensive lens to understand how internal consistency, leadership, flagship programs, infrastructure, and strategic communication collectively influence public perception and educational choice.